Changes in Cardiopulmonary Capacity Parameters after Surgery: A Pilot Study Exploring the Link between Heart Function and Knee Surgery - Andrea Segreti; Chiara Fossati; Luigi Maria Monticelli; Daniele Valente; Dajana Polito; Emiliano Guerra; Andrea Zampoli; Giorgio Albimonti; Biagio Zampogna; Sebastiano Vasta; Rocco Papalia; Raffaele Antonelli Incalzi; et al. (Journal of Functional Morphology and Kinesiology)
Background: A knee injury in an athlete leads to periods of forced exercise interruption. Myocardial work (MW) assessed by echocardiographic and cardiopulmonary exercise testing (CPET) are two essential methods for evaluating athletes during the period following injury. However, compared to pre-surgery evaluations, the variations in cardiovascular parameters and functional capacity assessed by these methods after surgery remain unclear. Methods: We evaluated 22 non-professional athletes aged 18–52, involved in prevalently aerobic or alternate aerobic/anaerobic sports activities, who were affected by a knee pathology requiring surgical treatment. The evaluation was performed at rest using transthoracic echocardiography, including MW assessment, and during exercise using CPET. Each athlete underwent the following two evaluations: the first before surgery and the second after surgery (specifically at the end of the deconditioning period). Results: Resting heart rate (HR) increased significantly (from 63.3 ± 10.85 to 71.2 ± 12.52 beats per minute, p = 0.041), while resting diastolic and systolic blood pressure, forced vital capacity, and forced expiratory volume in the first second did not show significant changes. Regarding the echocardiographic data, global longitudinal strain decreased from −18.9 ± 1.8 to −19.3 ± 1.75; however, this reduction was not statistically significant (p = 0.161). However, the global work efficiency (GWE) increased significantly (from 93.0% ± 2.9 to 94.8% ± 2.6, p = 0.006) and global wasted work (GWW) reduced significantly (from 141.4 ± 74.07 to 98.0 ± 50.9, p = 0.007). Additionally, the patients were able to perform maximal CPET at both pre- and post-surgery evaluations, as demonstrated by the peak respiratory exchange ratio and HR. However, the improved myocardial contractility (increased GWE and decreased GWW) observed at rest did not translate into significant changes in exercise parameters, such as peak oxygen consumption and the mean ventilation/carbon dioxide slope. Conclusions: After surgery, the athletes were more deconditioned (as indicated by a higher resting HR) but exhibited better resting myocardial contractility (increased GWE and reduced GWW). Interestingly, no significant changes in exercise capacity parameters, as evaluated by CPET, were found after surgery, suggesting that the improved myocardial contractility was offset by a greater degree of muscular deconditioning.